2017
DOI: 10.1016/j.celrep.2016.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Programming of Lifespan by FOXO Inhibition on Sugar-Rich Diets

Abstract: SummaryConsumption of unhealthy diets is exacerbating the burden of age-related ill health in aging populations. Such diets can program mammalian physiology to cause long-term, detrimental effects. Here, we show that, in Drosophila melanogaster, an unhealthy, high-sugar diet in early adulthood programs lifespan to curtail later-life survival despite subsequent dietary improvement. Excess dietary sugar promotes insulin-like signaling, inhibits dFOXO—the Drosophila homolog of forkhead box O (FOXO) transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 48 publications
2
75
0
1
Order By: Relevance
“…This effect could be ascribed to the sugar-rich diet-mediated induction of insulin-like signaling, which in turn inhibits dFoxO activity and suppresses dFoxO target genes encoding epigenetic regulators in the fat body. Their data underscore the importance of dFoxO in linking overnutrition to lifespan attenuation in Drosophila melanogaster (Dobson et al 2017). …”
Section: Foxo6 In Longevitymentioning
confidence: 89%
See 1 more Smart Citation
“…This effect could be ascribed to the sugar-rich diet-mediated induction of insulin-like signaling, which in turn inhibits dFoxO activity and suppresses dFoxO target genes encoding epigenetic regulators in the fat body. Their data underscore the importance of dFoxO in linking overnutrition to lifespan attenuation in Drosophila melanogaster (Dobson et al 2017). …”
Section: Foxo6 In Longevitymentioning
confidence: 89%
“…Indeed, there is evidence that dFoxO is not required for dietary restriction-induced lifespan extension in Drosophila melanogaster , although dFoxO modulates this process (Giannakou et al 2008; Hwangbo et al 2004; Min et al 2008). In a recent study, Dobson and colleagues took an opposite approach to address whether dFoxO is liable for the overnutrition-elicited reduction of lifespan in Drosophila melanogaster (Dobson et al 2017). They demonstrate that even transient feeding with a sugar-rich diet in early adulthood could produce a long-lasting detrimental effect on subsequent survival in female flies.…”
Section: Foxo6 In Longevitymentioning
confidence: 99%
“…Thus, it is possible for expression measures to trend in the same direction in DR and HS. Further, Dobson et al [70] found that excess sugar diets in young adult flies inhibited foxo and reduced survival in middle and old age. While we did not measure lifespan and fecundity here, our data showed mixed pattern of foxo activation in across diet tissue combinations, and these mapped to many coexpression modules (Table S5) which may be due to the relatively young age (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Major nutrient-sensing pathways, such as insulin and TOR signaling, are highly conserved between flies and mammals and techniques for studying aging in flies are well-established (Piper & Partridge 2017). High-sucrose treatment (1.0 M compared to 0.15 M controls) reduces Drosophila lifespan (Na et al 2013), even with transient exposure (1.2 M compared to 0.15 M controls) in young adults (Dobson et al 2017). The type of sugar is important, as sucrose is more detrimental than glucose or fructose (Lushchak et al 2014).…”
Section: Introductionmentioning
confidence: 99%